DAMPAK KINERJA KEUANGAN DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Rahayu, Ernia Christy; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the impact of the financial performance and the disclosure of corporate social responsibility of the firm value. Sample selection method is done by using purposive sampling method and 34 manufacturing companies which have published their financial statements in 2011-2013 periods in Indonesia Stock Exchange (www.idx.co.id). The data analysis has been done by using the multiple regression analysis and the independent variables which are proxy by Return on Asset and Corporate Social Responsibility (CSR) which are proxy by the CSDI to the firm value which is proxy by Tobins Q. The result of the research shows that based on t-test with its significant level is < 0.05. It gives the results that ROA has significant level of 0,000 with the result of t-test 3.462 and CSR has significant level 0,001 with the result of t-test 3.667. It can be concluded that the CSR and the ROA has positive and significant influence to the firm value. It means the financial performance is measured by the ability of the company to generate profits (ROA) will attract the investors to conduct investment. The enhancement of investment interest will be followed by the enhancement in the firm value. Meanwhile, that when the level of CSR (more company disclosure of social item and the better the quality level of expression) is high, the firm value is high as well. Keywords: kinerja keuangan, corporate social responsibility, nilia perusahaan.